2018
DOI: 10.2478/ssa-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Mineral matter composition of drained floodplain soils in north-eastern Poland

Abstract: Soils in two river valleys (Rozoga and Omulew) in north-eastern Poland were investigated. The valleys are located on a sandy outwash plain formed during the Vistulian (Weichelian) Glaciation. The soils are drained, used as meadows and classified as Fluvic Umbric Gleysol, Fluvic Mollic Gleysol, and Eutric Fluvic Histic Gleysol (IUSS Working Group WRB 2015). The aim of the study was to identify the composition of mineral matter and to determine the types of clay minerals and intermediate stages of clay minerals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Periodic flooding is also important for the functioning of valley ecosystems, directly affecting the moisture content of the surface layers of soils, as a result of which, soils in naturally functioning valleys retain a relatively high moisture content (in both topsoil and subsoil horizons), even in dry periods [19]. Furthermore, floods increase the nutrient content in soils, resulting in a specific floristic composition, as well as increased potential agricultural suitability [20][21][22]. Originally, vast areas of alluvial soils on the flooding terraces were covered with riparian forests [23,24], currently being among one of the most severely threatened forest communities in Europe [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Periodic flooding is also important for the functioning of valley ecosystems, directly affecting the moisture content of the surface layers of soils, as a result of which, soils in naturally functioning valleys retain a relatively high moisture content (in both topsoil and subsoil horizons), even in dry periods [19]. Furthermore, floods increase the nutrient content in soils, resulting in a specific floristic composition, as well as increased potential agricultural suitability [20][21][22]. Originally, vast areas of alluvial soils on the flooding terraces were covered with riparian forests [23,24], currently being among one of the most severely threatened forest communities in Europe [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…These reports have documented large water capacity of heavy-textured alluvial soils, particularly in the Wisła delta, while susceptibility for drought (after drainage) of coarse-textured soils in the valleys of central and southern Poland. Fine-textured topsoil horizons of alluvial soils have high exchange cation capacity and ability to adsorb macronutrients, as well as support stabilisation of organic matter (Banach-Szott et al, 2018;Brogowski and Okołowicz, 2008;Brogowski and Kwasowski, 2014;Dąbkowska-Naskręt, 1990;Długosz et al, 2018;Kabała et al, 2002;Kalembasa and Becher, 2010;Kobierski and Banach-Szott, 2022;Malinowski, 2008;Malinowski et al, 2004;Niedźwiedzki et al, 2011;Orzechowski et al, 2005;Woźniak, 1998). Strzemski et al (1973) have concluded that the thickness of the fine-textured topsoil (above the sandy subsoil), along with the depth of mean groundwater table, decide about the productivity of arable alluvial soils in Poland.…”
Section: Crucial Properties Of Alluvial Soils In Polandmentioning
confidence: 99%
“…In river valleys, soils enriched with organic matter occur very often [23]. Floodplain organic carbon accumulation as well as soil development depend on coastal flooding and sedimentation [24].…”
Section: Introductionmentioning
confidence: 99%
“…Organic C stocks in floodplain soils have been well described in the literature [23,24,[34][35][36], but still little is known about the quality of organic matter, including the molecular characteristics of humic substances, in these areas. River valleys are a mosaic of terrestrial and aquatic environments.…”
Section: Introductionmentioning
confidence: 99%